Evaluation of Policies for the Implementation of Social Welfare for Women in Socio-Economic Vulnerabilities in Sukabumi City - Rayhan Septa Rivaldi; Tuah Nur; M Rijal Amirulloh (Program Pascasarjana Universitas Negeri Makassar, 2022)
The purpose of this study is to describe and find out about the Evaluation of Policies for the Implementation of Social Welfare for Socio-Economic Vulnerable Women in Sukabumi City. In this study, the research method used was a qualitative method with a descriptive approach. The analytical techniques in this study were data reduction, data presentation, and analysis. conclusion. The results showed that on the Context Evaluation dimension, the welfare goals for WRSE can be said to be good, it's just that the existing budget constraints make the implementation not run properly. In the Input Evaluation dimension, the increase in the social welfare of people with WRSE has not been significant. In the Process Evaluation dimension, the obstacles experienced by KUBE members who are WRSE sufferers, are overall due to the lack of attention and thoroughness from the policy implementers towards the KUBE they foster. In the Product Evaluation dimension, the existence of this empowerment program will have a positive impact on the lives of themselves and other WRSE sufferers, but there are still improvements from the Sukabumi City Social Service as policy implementers and decision makers in every KUBE activity.